Self-Efficacy of 12th Grade Students in Physics Learning on Islamic, Private, and Public Schools - Wardani, Dwisri; Purwaningsih, Endang; Diantoro, Markus (Department of Physics Education, Universitas Mataram, 2025)
This study compares students' self-efficacy in physics learning across three types of schools: Islamic schools, public schools, and private schools. A quantitative research method was employed, focusing on twelfth-grade students during the 2024/2025 academic year. The data were collected using a questionnaire adapted from the Physics Learning Self-Efficacy (PLSE) instrument, which included 31 questionnaire items covering five key indicators. The responses were analyzed using one-way ANOVA with a 5% significance level. The findings indicated that students from Islamic schools demonstrated the highest mean self-efficacy in physics learning, followed by those in public and private schools. Among the five indicators, the Everyday Application (EA) indicator emerged as the strongest across all three school types, particularly in Islamic schools. Further analysis using the Tukey HSD test revealed a significant difference in self-efficacy levels between Islamic schools and both public and private schools, while no significant difference was observed between public and private schools. These results emphasized the critical role of a supportive learning environment, comprehensive teaching strategies, and enhanced practicum activities in fostering students' self-efficacy in physics learning.